I have asked a question or two like this one before and I've tryed to use similar methods to prove this identity(?), but I failed. By using WA it seems that numerically the LHS=RHS

$$ \left(\frac{\pi}{3} \right)^{2}=1+2\sum_{k=1}^{\infty}\frac{(2k+1)\zeta(2k+2)}{3^{2k+2}} $$ But a rigorous proof would be better!

The other similar identity is $$ \left(\frac{\pi}{2}\right)^{2}=1+2\sum_{k=1}^{\infty}\frac{(2k-1)\zeta(2k)}{2^{2k}} $$

Thanks in advance.

  • 1
    $\begingroup$ Why, pray tell, close this question? $\endgroup$ – Ron Gordon Feb 19 '14 at 18:07

Exactly the same idea as in the linked similar identity by user "Grigory M" works for this.

$$\pi\cot(\pi x)=\frac{1}{x}-2\sum_{n=1}^\infty \zeta(2n)x^{2n-1}.$$

Taking derivatives:

$$\frac{\pi^2}{\sin^2(\pi x)}=x^{-2}+2\sum_{n=1}^\infty (2n-1)\zeta(2n)x^{2n-2}$$

Change the index of summation to $2n=2k+2$. Thus, write the sum

$$\sum_{n=1}^\infty (2n-1)\zeta(2n)x^{2n-2}=\zeta(2)+\sum_{k=1}^\infty (2k+1)\zeta(2k+2)x^{2k}.$$

Then $\zeta(2)=\pi^2/6$, and evaluate both sides at $x=1/3$. You have:

$$\frac{4\pi^2}{3}=9+\frac{\pi^2}{3}+2\sum_{k=1}^\infty \frac{(2k+1)\zeta(2k+2)}{3^{2k}}$$

Carrying over the $\pi^2/3$ and dividing both sides by 9 gives:

$$\left(\frac{\pi}{3}\right)^2=1+2\sum_{n=1}^\infty \frac{(2k+1)\zeta(2k+2)}{3^{2k+2}}$$

  • $\begingroup$ In the same spirit what would you sugest for $\left(\frac{\pi}{4}\right)^{2}=1+\cdots$? $\endgroup$ – Neves Feb 19 '14 at 17:05
  • $\begingroup$ @Neves: you have two options at your disposal: 1) Taking $k$ derivatives which gives you factors like (2n-1)(2n-2)...(2n-k) infront of your zeta 2) Shifting index of summation For $\pi=4$, a good thing to try is the exact same procedure above, and plug in $x=1/4$. $\endgroup$ – Alex R. Feb 19 '14 at 17:07
  • $\begingroup$ Can that first cotangent identity be proven without the aid of complex analysis? $\endgroup$ – Lucian Feb 20 '14 at 4:27

The sum

$$\sum_{k=1}^{\infty} \frac{(2 k+1) \zeta(2 k+2)}{3^{2 k+2}} = \sum_{n=1}^{\infty} \frac1{9 n^2}\sum_{k=1}^{\infty} \frac{2 k+1}{(9 n^2)^k}$$

from the definition of the zeta function. The inner sum is a geometrical sum and its derivative. In essence, it is simple to derive the following:

$$\sum_{k=1}^{\infty} (2 k+1) r^k = \frac{r (3-r)}{(1-r)^2}$$

Here, $r=1/(9 n^2)$, so we have the sum

$$\sum_{n=1}^{\infty}\frac1{9 n^2} \frac{27 n^2-1}{(9 n^2-1)^2} = -\sum_{n=1}^{\infty} \frac1{9 n^2} + \sum_{n=1}^{\infty} \frac{9 n^2+1}{(9 n^2-1)^2}$$

The first sum is easy ($-\pi^2/54$), so let's attack the second. This may be accomplished via residues. Without going into details, I state the result:

$$\sum_{n=-\infty}^{\infty} f(n) = -\sum_{k} \operatorname*{Res}_{z=z_k} \pi \, \cot{(\pi z)} \, f(z)$$

Here, $f(z) = (9 z^2+1)/(9 z^2-1)^2$. The poles of $f$ are at $z_{\pm}=\pm 1/3$. The sum of the above residues at these poles are

$$\pi \sum_{\pm} \left [\frac{d}{dz} \frac{\cot{(\pi z)} (9 z^2+1)}{(3 z \pm 1)^2} \right ]_{z=\pm 1/3} = -\frac{4 \pi^2}{27}$$

$$\implies \sum_{n=1}^{\infty} \frac{9 n^2+1}{(9 n^2-1)^2} = \frac{2 \pi^2}{27} - \frac12 $$


$$1+2 \sum_{k=1}^{\infty} \frac{(2 k+1) \zeta(2 k+2)}{3^{2 k+2}} = -\frac{\pi^2}{27} + \frac{4 \pi^2}{27} = \frac{\pi^2}{9}$$

as was to be shown.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.